You are on page 1of 3

# 2013 4.

(a) Two particles of masses 6 kg and 7 kg are connected by a light inextensible string passing over a smooth light fixed pulley which is fixed to the ceiling of a lift. The particles are released from rest. Find the tension in the string
6 7

(i) when the lift remains at rest (ii) when the lift is rising vertically with constant acceleration 1 8 g. SOLUTION (i)

FNet = ma T W1 = 6a T 6 g = 6a....(1)
T a 6 kg 6 kg a T T 7 kg a

FNet = ma W2 T = 7 a 7 g T = 7 a....(2)
T 7 kg a

W1 = 6g

W1 = 6g

W2 = 7g

W2 = 7g

T 6 g = 6a....(1) 7 g T = 7 a....(2) g
1 = 13a a = 13 g m s 2

T 6 g = 6a....(1) T = 6a + 6 g
1 = 6( 13 g) + 6g 84 = 13 g N

= 63.3 N

## Kieran Mills & Tony Kelly (www.studentxpress.ie)

(ii)

1g 8

FNet = ma T W1 = 6(a + 1 8 g)
1 T 6 g = 6( a + 8 g )...(1)

(i)
a T 6 kg T 7 kg a

T
g (a - 1 8 )

T 6 kg
g (a + 1 8 )

7 kg

W1 = 6g

W1 = 6g

W2 = 7g

W2 = 7g

## T 6 g = 6(a + 1 8 g )...(1) 7 g T = 7( a 1 8 g )...( 2)

6 T 6 g = 6a + 8 g 7 7 g T = 7a 8 g

g
9 8

= 13a 1 8 g g = 13a

T 6 g = 6(a + 1 8 g )...(1)
9 T = 6( 104 g+1 8 g) + 6g

9 g m s 2 a = 104

T = 189 26 g N = 71.24 N

(b) A light inextensible string passes over a smooth fixed pulley, under a movable smooth pulley of mass m3, and then over a second smooth fixed pulley. A particle of mass m1 is attached to one end of the string and a particle of mass m2 is attached to the other end. The system is released from rest. Find the tension in the string in terms of m1, m2 and m3.
m1

m3 m2

## Kieran Mills & Tony Kelly (www.studentxpress.ie)

SOLUTION Say the 2 masses are accelerating upwards and the movable pulley is accelerating downwards. If m1 accelerates up with acceleration a the moveable pulley accelerates down with an acceleration of half of this. Similarly if m2 accelerates up with acceleration b the movable pulley accelerates down with half of this acceleration.

1a 2

+1 2b

T m3 T a m1 W3 = m3g

T b m2 W2 = m2g

W1 = m1g

## FNet = ma T W2 = m2b T m2 g = m2b....(2)

Substitute the values of a and b into Eqation (3). m3 g 2T = 1 2 m3 ( a + b)....( 3) T T m3 g 2T = 1 g+ g 2 m3 m2 m1 mT mT m3 g 2T = 3 + 3 m3 g (2m1m2 ) 2m1 2m2 2m1m2 m3 g 4m1m2T = m2 m3T + m1m3T 2m1m2 m3 g 4m1m2 m3 g = 4m1m2T + m2 m3T + m1m3T 4m1m2 m3 g = (4m1m2 + m2 m3 + m1m3 )T T = 4m1m2 m3 g 4m1m2 + m2 m3 + m1m3

T m2 g = m2b....(2) T b= g m2